L’importance des mécanismes de régulation temporelle dans le travail des opératrices de métiers à fibres libérées relativement à l’automatisation des machines et au travail de nuit - Régis Lachance (Perspectives Interdisciplinaires sur le Travail et la Santé)
Contrary to the initial predictions of mill personnel, the work of the open-end loom operators appears to involve more muscular demands than was originally believed, on what where considered to be fully automatic machines. Also, the fact of working on the night shift seems to exacerbate the difficulties encountered by the workers, since 67 % of the accidents occurred during that period. The study described here was designed to go beyond the posture analysis and dynamometric measures that appear to be a major element in the design of the looms. A work sequence activity and temporal analysis revealed the operators’ previously underestimated expertise in modifying their activities to adapt to different working conditions. Adjustments in the cleaning procedure appear to be the principal regulation mechanism and point to the equal importance of both mental and physical requirements for the workers.